2018
DOI: 10.6018/j/350021
|View full text |Cite
|
Sign up to set email alerts
|

Evolución de las metas académicas en función del sexo y la edad y su influencia en el rendimiento académico en adolescentes murcianos

Abstract: Las metas académicas constituyen una de las variables más importantes desde el punto de vista motivacional para explicar las diferentes razones por las que los estudiantes se implican en las tareas y actividades de aprendizaje. En este estudio se analiza la evolución de las metas académicas y la influencia de éstas en el rendimiento a lo largo de los 6 años que dura la enseñanza secundaria en función de variables sociodemográficas (sexo, edad y curso académico) en una muestra de 546 adolescentes murcianos. El … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
0
5
0
8
Order By: Relevance
“…In addition, it is expected that, as the student progresses in his studies, he will present different goals of achievement, due to his perception of the various curricular disciplines or the relevance of their contents to his vocational projects [69,71] In this sense, [77,78] concluded that students oriented towards intrinsic goals have a better academic performance, while students whose goals focus on the self, end up showing worse performance.…”
Section: Burnout Motivation and Low Academic Performance In Universmentioning
confidence: 99%
“…In addition, it is expected that, as the student progresses in his studies, he will present different goals of achievement, due to his perception of the various curricular disciplines or the relevance of their contents to his vocational projects [69,71] In this sense, [77,78] concluded that students oriented towards intrinsic goals have a better academic performance, while students whose goals focus on the self, end up showing worse performance.…”
Section: Burnout Motivation and Low Academic Performance In Universmentioning
confidence: 99%
“…Similarly, they are more interested in personal, social, economic and political independence. These goals stimulate their motivation to achieve just as girls pursue academic goals for the degree (Arnaiz-Sánchez et al, 2019;Dweck & Elliot, 2005;Ruiz-Esteban et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Las orientaciones a metas académicas se han estudiado en diversos contextos educativos, al considerarse una de las variables más importantes desde la perspectiva motivacional para explicar por qué los estudiantes se interesan y se involucran en las tareas para el aprendizaje (Ruiz-Esteban et al, 2018). A partir de las evidencias presentadas por De la Fuente (2004) se reconoce que los estudios sobre motivación están centrados en los enfoques de metas, motivación intrínseca-extrínseca.…”
Section: Metas Académicas Y Perfiles Motivacionalesunclassified
“…Diversas investigaciones han evidenciado los beneficios que tiene considerar en el ámbito académico las metas múltiples en el estudiantado (Castejón, Gilar, Miñano y Veas, 2016;Estévez, Rodríguez, Valle, Regueiro y Piñeiro, 2016;Franco, González Cabanach, Souto-Gestal y González, 2017;Ruiz-Esteban, Méndez y Díaz-Herrero, 2018), así como los perfiles motivacionales en relación con la autoeficacia (Becerra-González y Reidl, 2015;Valle, Regueiro, Rodríguez, Piñeiro, Freire y Suárez, 2015;Ferradás, Freire, Regueiro y Estévez, 2017;Ferradás, Freire, Rodríguez y Piñeiro, 2018).…”
Section: Introductionunclassified